Plasma metabolite biomarkers of boiled and filtered coffee intake and their association with type 2 diabetes risk. (9th December 2019) - Shi, L.; Brunius, C.; Johansson, I.; Bergdahl, I.A.; Rolandsson, O.; van Guelpen, B.; Winkvist, A.; Hanhineva, K.; Landberg, R.
Abstract: Background: Habitual coffee intake has been associated with a lower risk of developing type 2 diabetes (T2D), but few studies used biomarkers to reflect intake and investigated different coffee brews, that is boiled and filtered, separately. Objectives: To identify plasma metabolites associated with boiled or filtered coffee intake and to examine their association with T2D risk in Swedish adults. Methods: In a case–control study nested within the Västerbotten Intervention Programme, baseline plasma samples from 421 case–control pairs and samples from a subset of 149 pairs at a 10‐year follow‐up were analysed using untargeted LC‐MS metabolomics. We identified metabolites associated with food frequency questionnaires (FFQ)‐estimated coffee intake and assessed odds ratios of T2D. Results: In total, 24 and 32 metabolites were associated with boiled or filtered coffee intake. We determined robust metabolite panels for highly specific prediction of boiled or filtered coffee. We observed an inverse association between the metabolite panel of filtered coffee and T2D risk. No association with T2D was observed for the panel of boiled coffee intake. Similar results were observed for FFQ‐estimated coffee intake. Conclusions: We identified plasma metabolites specifically associated with boiled or filtered coffee intake, which might be used as selective biomarkers. Our study supports a protective role of habitual intake of filtered coffee on T2D development. The lack of association for boiled coffee intake might be due to the lack of a protective effect of boiled coffee or due to the limited number of boiled coffee consumers in this population, but it warrants further investigation. Abstract :